Impacto Socioeconómico de la COVID-19 en el Departamento del Tolima (2022)
Given the COVID-19 pandemic, the Colombian government, as in most countries, had a set of health measures and changes in daily routine at the economic, social and political levels in order to control the rapid spread of the virus. These restrictions triggered a major economic recession worldwide, for example, the collapse of the Gross Domestic Product (GDP) has been one of the main consequences, which led to a drop in economic growth. Additionally, the pandemic generated consequences in the population, which led to an increase in deaths and, in turn, to an increase in the mortality rate at the national and departmental levels. Under this scenario, it is necessary to know the socioeconomic situation in terms of the current health crisis, specifically for Tolima, because although there is information worldwide, from Latin America and Colombia, there are few regional studies that relate the consequences of the same in the economic sectors of the department, the evolution of the virus and the severity in people's health. Therefore, the objective of this document is to analyze the socioeconomic situation before and after the pandemic and the impact of the mandatory isolation measures to prevent the spread of COVID-19 in the department of Tolima during the period 2010-2020. A descriptive mixed-type research was developed in which a review of secondary sources of information was carried out for three variables: unemployment rate, GDP and mortality rate, with which the simple linear regression analysis was carried out using the Excel program software. When comparing the unemployment rate of the region with the data at the national level, it is observed that the department shows higher values, it is worth noting that Ibagué (capital of Tolima, which concentrates a large percentage of the inhabitants of the territory), according to Hernández Rodríguez (2020), since 2000 it has presented high rates of unemployment, underemployment and informality, even above the national average. Through the linear regression model, it was possible to establish the possible determinants of COVID-19 against the unemployment rate and GDP for the department of Tolima, where based on the studies by McKibbin and Fernando (2020), the incidence of COVID-19 for its mortality rate was low to medium. There was a greater relationship between the mortality rate and unemployment, which can translate into greater informality in the trades. The economic structure of the department is based on the agricultural sector, but unemployment in the different sectors and this one in particular has been gradually reduced in the last ten years, so the incidence of the pandemic does not change the trend, and even does not reach the lower historical values.